2016
DOI: 10.1108/s1530-353520160000010011
|View full text |Cite
|
Sign up to set email alerts
|

Coparenting in the Digital Era: Exploring Divorced Parents’ Use of Technology

Abstract: Purpose À The current study was designed to examine how and why divorced parents use computers and the Internet for communication with their coparent and with their child(ren). Methodology/approach À The current study utilized the uses and gratification perspective. A subsample of 178 divorced parents with at least one child aged 25 or younger from a larger research project participated. Parents were recruited to participate in a 15-minute online survey through email listservs with a nationwide and demographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 27 publications
(25 reference statements)
0
22
1
4
Order By: Relevance
“…Dworkin et al. () examined separated parents’ use of technology as a medium of communication for parenting issues. Amongst a sample of 178, the study indicated that divorced parents were active users of technology in facilitating the co‐parental relationship.…”
Section: Post‐separation Parenting and Use Of Communication Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Dworkin et al. () examined separated parents’ use of technology as a medium of communication for parenting issues. Amongst a sample of 178, the study indicated that divorced parents were active users of technology in facilitating the co‐parental relationship.…”
Section: Post‐separation Parenting and Use Of Communication Technologiesmentioning
confidence: 99%
“…Research looking at the specific use of computing technologies (CTs) by separated or separating co‐parents in the context of the ongoing parental relationship, however, is limited, with a small number of exceptions (Chapman, Ganong, & Coleman, ; Doucet, ; Dworkin, McCann, & McGuire, ). This small body of research explores the ways co‐parents use or misuse CTs for purposes of the parental relationship in contexts of cooperation and conflict.…”
mentioning
confidence: 99%
“…Despite the prevalence of ICT in today's society and the growing level of support for this technology among professionals within the family court system, little is known about the impact of virtual contact on facilitating, supporting, maintaining, or enhancing parent-child relationships postseparation and divorce. Few empirical studies have examined the use of virtual parent-child contact within the context of separation and divorce offering some advancements within the field (Castelain-Meunier, 1997; Dworkin, McCann, & McGuire, 2016;Ganong, Coleman, Feistman, Jamison, & Markham, 2012;Gollop & Taylor, 2012;Saini et al, 2013;Wolman & Pomerance, 2012;Yarosh, Chew, & Abowd, 2009).…”
Section: Ict In Separated and Divorced Families: Literature Reviewmentioning
confidence: 99%
“…The few studies available have shown mixed findings on whether families experienced VPT as positive, functional, and practical (Castelain-Meunier, 1997;Dworkin et al, 2016;Wolman & Pomerance, 2012) or as a frustrating means of communication (Castelain-Meunier, 1997; Gollop & Taylor, 2012). For instance, parents whose children had relocated viewed VPT negatively and felt their parenting role was more virtual than real (Castelain-Munier, 1997;Gollop & Taylor, 2012).…”
Section: Ict In Separated and Divorced Families: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation